Dampak Faktor Keuangan dan Ukuran Perusahaan terhadap Financial Distress Perusahaan Food and Beverage yang Tercatat di BEI Tahun 2020-2022 - Febiyana Febiyana; Siti Alliyah (Universitas Nusantara PGRI Kediri, 2025)
The purpose of this study is to analyze the impact of leverage, liquidity, company size, and profitability on the financial distress of food and beverage companies listed on the IDX in 2020-2022. Purposive sampling is the sample selection method, the regression data analysis is multiple linear and the type of data is quantitative. This study reveals that company size and leverage have a significant negative impact, while liquidity is positive and insignificant. Profitability has a positive and significant impact on financial distress. This study shows that leverage has a significant negative impact on financial distress. Liquidity has a positive but insignificant impact on financial distress. Profitability has a significant positive impact on financial distress. Company size has a significant negative impact on financial distress.